Association between dietary pattern and cardiometabolic risk in children and adolescents: a systematic review - Naruna Pereira Rocha; Luana Cupertino Milagres; Giana Zarbato Longo; Andréia Queiroz Ribeiro; Juliana Farias de Novaes (Brazilian Society of Pediatrics, 2017)
Objective: To evaluate the association between dietary patterns and cardiometabolic risk factors in children and adolescents. Data source: This article followed the recommendations of PRISMA, which aims to guide review publications in the health area. The article search strategy included searches in the electronic databases MEDLINE via PubMed, Scopus, and LILACS. There was no date limitation for publications. The descriptors were used in English according to MeSH and in Portuguese according to DeCS. Only articles on dietary patterns extracted by the a posteriori methodology were included. The question to be answered was: how much can an "unhealthy" dietary pattern influence biochemical and inflammatory markers in this population? Data synthesis: The studies showed an association between dietary patterns and cardiometabolic alterations. The patterns were characterized as unhealthy when associated to the consumption of ultraprocessed products, poor in fiber and rich in sodium, fat, and refined carbohydrates. Despite the associations, in several studies, the strength of this association for some risk markers was reduced or lost after adjusting for confounding variables. Conclusion: There was a positive association between "unhealthy" dietary patterns and cardiometabolic alterations in children and adolescents. Some unconfirmed associations may be related to the difficulty of assessing food consumption. Nevertheless, studies involving dietary patterns and their association with risk factors should be performed in children and adolescents, aiming at interventions and early changes in dietary habits considered to be inadequate.